Laplacian Minimum Covering Randic Energy of A Graph - Kanna, M.R. Rajesh; Jagadeesh, R. (Communications in Mathematics and Applications, 2018)
Randic energy was first defined in the article [6]. Using minimum covering set, we have introduced in this article Laplacian minimum covering Randic energy \(LRE_C(G)\) of a graph \(G\). This article contains computation of Laplacian minimum covering Randic energies for some standard graphs like star graph, complete graph, crown graph, complete bipartite graph and cocktail graph. Atthe end of this article upper and lower bounds for Laplacian minimum covering Randic energy are also presented.
Keywords: Minimum covering set; Minimum covering Randic matrix; Laplacian minimum covering Randic matrix; Laplacian minimum covering Randic eigenvalues; Laplacian minimum covering Randic energy